2020
DOI: 10.1007/s40145-020-0425-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel optical properties and induced magnetic moments in Ru-doped hybrid improper ferroelectric Ca3Ti2O7

Abstract: Hybrid improper ferroelectric Ca3Ti2O7 and Ca3Ti19Ru0.1O7 ceramics were successfully synthesized by conventional solid-state reaction method. Two strongest diffraction peaks located around 2θ = 33° shifted towards the lower angle region with Ru substitution, reflecting structure variation. Grain growth and higher oxygen vacancy concentration after doping resulted in a reduction in the coercive field about 20 kV/cm. Optical bandgap estimated by UV-vis diffuse reflectance (DR) spectrum and X-ray photoelectron sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…It shows the interaction between magnetic atoms is bridged by the O sites, which further confirms that the double exchange between magnetic atoms (Mn 3+ /Ru 3+ –O–Mn 4+ ) is introduced from the change of valence after doping. It has been reported that Ru‐doping induced the weak ferromagnetism in Ca 3 Ti 2 O 7 18 . The layer‐by‐layer contribution of magnetic moments from magnetic atoms in Ru‐doped Ca 3 Mn 2 O 7 systems are illustrated in Figure 10C,D.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…It shows the interaction between magnetic atoms is bridged by the O sites, which further confirms that the double exchange between magnetic atoms (Mn 3+ /Ru 3+ –O–Mn 4+ ) is introduced from the change of valence after doping. It has been reported that Ru‐doping induced the weak ferromagnetism in Ca 3 Ti 2 O 7 18 . The layer‐by‐layer contribution of magnetic moments from magnetic atoms in Ru‐doped Ca 3 Mn 2 O 7 systems are illustrated in Figure 10C,D.…”
Section: Resultsmentioning
confidence: 86%
“…It was reported that magnetism has been increased with Ru substitution in a number of other perovskite systems 18 ; therefore, Ru doping is of great significance in improving the magnetic properties of ceramic materials. In this work, we choose B‐site doping to tune the magnetic properties of Ca 3 Mn 2 O 7 by replacing Mn 4+ with Ru 3+ ion.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that anionic electrons had a significant impact on the magnetism of electrides by acting as magnetism centers, which are significantly different from the traditional magnetic materials. To study the influence of anionic electrons on the magnetism of Ba 5 P 3 , four magnetic configurations, a ferromagnetic (FM) and three antiferromagnetic (AFM) states, were prepared using the code Supercell (Figure S4). The total energies of magnetic configurations are lower than that of the nonmagnetic (NM) state (−4.890 eV/atom), and particularly the AFM1 state possesses the lowest energy (−4.905 eV/atom).…”
Section: Results and Discussionmentioning
confidence: 99%
“…A piece of the cleaved ab plane EuInO 3 crystal with 28 μm thickness was used as the sample. The positive-up-negative-down (PUND) method was adopted to get rid of leakage current and capacitance contribution. , …”
Section: Methodsmentioning
confidence: 99%